A Study of Super Refractory Status Epilepticus from India - Misra, Usha K.; Kalita, Jayantee; Dubey, Deepanshu (Frontiers in Neurology, 2017)
Background: Super refractory status epilepticus (SRSE) is an important and recently recognized neurological emergency. Purpose: In view of paucity of studies on SRSE, we report the frequency, etiology and outcome of SRSE. Methods: In a hospital based observational study during 2013 to 2016, consecutive patients with SRSE (persistence of status epilepticus for 24 hours or more, or recurrence of SE on weaning of intravenous anaesthetic) were included. The demographic, clinical and laboratory data were obtained and the severity of SE was defined using Status Epilepticus Severity Score (STESS). The outcome was defined as control of SE, hospital death and functional status at the time of discharge. Results: Fourteen (13%) patients developed SRSE. Their median age was 27.5 (2-70) years and four were below 18 years of age. The etiology of SRSE was metabolic encephalopathy and encephalitis in five patients each, cerebral venous sinus thrombosis in one and miscellaneous disorders in three patients. Six (43%) patients died. The patients with SRSE had higher admission STESS (p = 0.04), and longer intensive care unit (P < 0.01) and hospital (P = 0.004) stay compared to non-SRSE group. The patients with treatable etiology had better outcome. Conclusion: Super refractory status epilepticus occurred in 13% patients with SE and 43% of them died. The SRSE patients with treatable etiology had a better outcome.